Isoniazid preventive therapy-related adverse events among Malawian adults on antiretroviral therapy: A cohort study. Issue 39 (30th September 2022) - Tsirizani-Galileya, Lufina; Milanzi, Elasma; Mungwira, Randy; Divala, Titus; Mallewa, Jane; Mategula, Donnie; Nampota, Nginache; Mwapasa, Victor; Buchwald, Andrea; Laurens, Matthew B.; Laufer, Miriam K.; Van Oosterhout, Joep J.
Abstract : Adverse events may be a cause of observed poor completion of isoniazid preventive therapy (IPT) among people living with HIV in high tuberculosis burden areas. Data on IPT-related adverse events (AE) from sub-Saharan Africa are scarce. We report IPT-related AEs, associated clinical characteristics, and IPT discontinuations in adults who were stable on antiretroviral therapy (ART) when they initiated IPT. Cohort study nested within a randomized, controlled, clinical trial of cotrimoxazole and chloroquine prophylaxis in Malawians aged ≥ 18 years and virologically suppressed on ART. Eight hundred sixty-nine patients were followed for a median of 6 months after IPT initiation. IPT relatedness of AEs was determined retrospectively with the World Health Organization case-causality tool. Frailty survival regression modeling identified factors associated with time to first probably IPT-related AE. The overall IPT-related AE incidence rate was 1.1/person year of observation. IPT relatedness was mostly uncertain and few AEs were severe. Most common were liver and hematological toxicities. Higher age increased risk of a probably IPT-related AE (aHR = 1.02; 95% CI 1.00–1.06; P  = .06) and higher weight reduced this risk (aHR = 0.98; 95% CI 0.96–1.00; P  = .03). Of 869 patients, 114 (13%) discontinued IPT and 94/114 (82%) discontinuations occurred at the time of a possibly or probably IPT-related AE. We observed a high incidence of mostly mild IPT-related AEs among individuals who were stable on ART. More than 1 in 8 persons discontinued IPT. These findings inform strategies to improve implementation of IPT in adults on ART, including close monitoring of groups at higher risk of IPT-related AEs.